Basal Area - Volume Relations for Eucalyptus grandis Crops - Pande, G. C.; Jain, R. C. (Indian Forester, 1974)
Large scale plantations are being raised in the country under the Five year plans. The main point of interest at any time is 'What is the volume of the crop?'. The direct measurement of volume is tedious and felling of sample trees may not be always possible. However two parameters viz. basal area (BA) of the crop and crop height (H) can be easily and quickly estimated. In the present study for E. grandis crops regressions of crop volume (both with and without bark) on the variable BA Ã— H have shown very high determination coefficients. Tables have been given to estimate volume based on these parameters. It has been noticed that, although at 5% level of probability, the regression is independent of quality classes, at a lower level of probability it may become dependent on quality class. However, when the number per hectare (N) another easily estimable parameter-is added as an extra variable in the regression equation, there is not only considerable reduction in the residual sum of squares, the regression becomes definitely more independent of the quality. The regression equations so developed for volume (both outside & inside bark) are given and two tables are given for No.=800/ha and 1600/ha; other tables are not given but can be formed by using the equations.